Pårørende i psykiatrien; fortid, nutid og fremtid – et forskningsoprids - Eckardt, Jens Peter (Nordisk tidsskrift for helseforskning, 2016)
Caregivers of persons with mental illness: a look into past, present and future research The purpose of this article is to summarize the author’s presentation on caregivers in psychiatry, held at the University of Copenhagen in March of 2016. The purpose of the lecture was to provide an outline of the history of the research focusing on caregivers of persons with mental illness, with some predictions of how future research in this field may be conducted. A secondary purpose was to raise awareness of the role caregivers can play in psychiatry, which over time has not been a major subject in the field of research.